IDENTIFIKASI JENIS MANGROVE DAN FAKTOR LINGKUNGAN TEMPAT TUMBUH MANGROVE DI DUSUN NAMA’EA NEGERI PELAUW PULAU HARUKU, MALUKU TENGAH - Latuconsina, Risano; Soselisa, Fanny; Sitanala, Merlin (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research aims to determine the type of mangrove vegetation in Nama'Ea Hamlet, Negeri Pelauw, Haruku Island District, Central Maluku Regency. This research uses qualitative descriptive analysis. Identification of the type of mangrove is done by looking at the shape of the roots, shape of the leaves, shape of the flowers and shape of the fruit. Based on the results of the analysis, 6 types of mangroves were found that grow on the coast of Nama'ea Hamlet, namely: Sonneratia alba, Rhizophora apiculata, Rhizophora stylosa, Rhizophora mucronata, Ceriops tagal and Bruguiera gymnorrizha. Environmental factors that influence mangrove growth are: The lowest temperature is 29 °C and the highest is 35 °C, the substrate condition at the research location is sandy and sandy mud, the water salinity is 19-30, the soil and water pH is 5-8, The mud depth measurement is 7 cm - 16 cm at the front, 7 cm - 21 cm in the middle and 6 cm - 41 cm at the back.